2022
DOI: 10.1017/dmp.2022.262
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of Patients’ Trust in Nurses During the COVID-19 Pandemic: A Mixed-Methods Study

Abstract: Objective: This study aimed to investigate the nurse-patient trust among in-patients in the context of the COVID-19 epidemic; it further analyzed the related influencing factors, which will provide a theoretical basis for developing corresponding measures. Methods: This study employed a mixed-method design and analyzed 149 patients at the Hongqi Hospital, affiliated with Mudanjiang Medical University, from December 2020 to February 2021. Quantitative analysis was carried out using the “N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…The importance of these factors has also been demonstrated in previous studies, some of which have shown that the quality of the hospital's physical environment and services has a significant impact on patient trust. 30,31 For example, a semi-structured telephone interview indicated that a welcoming physical environment was associated with higher TIP. 31 At the physician level, our data show that a physician's title level, demonstrated patience, and protection of patient privacy are key factors in gaining patient trust.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these factors has also been demonstrated in previous studies, some of which have shown that the quality of the hospital's physical environment and services has a significant impact on patient trust. 30,31 For example, a semi-structured telephone interview indicated that a welcoming physical environment was associated with higher TIP. 31 At the physician level, our data show that a physician's title level, demonstrated patience, and protection of patient privacy are key factors in gaining patient trust.…”
Section: Discussionmentioning
confidence: 99%
“…Otro estudio (26) también encontró que la confianza era la prioridad de la enfermera entre otras dimensiones de los valores profesionales de las enfermeras iraníes. Esta diferencia puede estar relacionada con mayores instalaciones, la propia competencia del enfermero y mejores condiciones de trabajo de los hospitales privados que los estatales (27) . La ubicación de esta investigación se realizó en hospitales educativos y gubernamentales donde diversas profesiones de la salud realizan práctica clínica en estos hospitales como estudiantes de enfermería, medicina, radiología, nutricionista y partería.…”
Section: Discussionunclassified